توظيف معايير النص عند روبرت دي بوجراند في التوجيه العقدي والفقهي للمذهب الإباضي : دراسة نصية - دغيشية، سعاد بنت سعيد بن علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aims to use Robert de Beaugrand's seven standards of text; cohesion, coherence, intentionality, acceptability, situationality, informativity and textuality in the light of paraphrasing of Aqedah and Islamic Jurisprudence. These standards are used to understand the meanings of the words and the structures. This study is conducted to explain the linguistic bases and principles from which the Ibadis Mazhab originates its doctrinal views. The researcher identifies the most important pillars of the Ibadis doctrine which form its doctrinal orientation and brings the views of the different Islamic sects closer. The researcher has analyzed six issues in the Aqedah and six issues in Jurisprudence. The conclusion of the study highlights a number of points. Most importantly, the use of the seven standards of text in the evidences the Ibadi scholars have deduced in their Aqedah and Jurisprudential doctrine did not depart from the Arab discourse because Quran and Sunnah are only understood through Arabic grammar and situational and cultural contexts of the text. Not only the seven standards of text of Robert de Beaugrand were emphazised through the evidences used by the Ibadi scholars, those seven standards enabled the researcher to illustrate the perspectives of Ibadhi doctrine in the meaning of the words and the reasons behind choosing their doctrinal views. The Aqedah and Jurisprudence views of the Ibadi Mazhab are based on the understanding of the legal texts through the comprehensive understanding of Arabic grammar, rhetoric and discourse as well as adopting the principle of the general decency of Allah, and the principle of Sharia law by adhering to Quran and Sunnah.